Measurement properties of patient-reported outcome measures (PROMs) in adults with obstructive sleep apnea (OSA): A systematic review. (August 2016) - Abma, Inger L.; van der Wees, Philip J.; Veer, Vik; Westert, Gert P.; Rovers, Maroeska
Summary: This systematic review summarizes the evidence regarding the quality of patient-reported outcome measures (PROMs) validated in patients with obstructive sleep apnea (OSA). We performed a systematic literature search of all PROMs validated in patients with OSA, and found 22 measures meeting our inclusion criteria. The quality of the studies was assessed using the consensus-based standards for the selection of health status measurement instruments (COSMIN) checklist. The results showed that most of the measurement properties of the PROMs were not, or not adequately, assessed. For many identified PROMs there was no involvement of patients with OSA during their development or before the PROM was tested in patients with OSA. Positive exceptions and the best current candidates for assessing health status in patients with OSA are the sleep apnea quality of life index (SAQLI), Maugeri obstructive sleep apnea syndrome (MOSAS) questionnaire, Quebec sleep questionnaire (QSQ) and the obstructive sleep apnea patient-oriented severity index (OSAPOSI). Even though there is not enough evidence to fully judge the quality of these PROMs as outcome measure, when interpreted with caution, they have the potential to add value to clinical research and clinical practice in evaluating aspects of health status that are important to patients.